2012
DOI: 10.1016/j.ymgme.2011.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis and vascular calcifications in alkaptonuria

Abstract: Alkaptonuria is a rare metabolic disorder of tyrosine catabolism in which homogentisic acid (HGA) accumulates and is deposited throughout the spine, large joints, cardiovascular system, and various tissues throughout the body. In the cardiovascular system, pigment deposition has been described in the heart valves, endocardium, pericardium, aortic intima and coronary arteries. The prevalence of cardiovascular disease in patients with alkaptonuria varies in previous reports . We present a series of 76 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…In the Cardiovascular Health Study, which looked at 5621 patients aged 65 or older, 1.8% were found to have aortic stenosis [7]. A series of 76 patients with alkaptonuria found aortic stenosis in 25% of patients over 65 [3]. Interestingly, unlike degenerative calcific aortic stenosis, the presence of stenosis was not correlated with the standard cardiovascular risk factors or age related calcification but was moderately correlated with the extent of joint involvement, another manifestation of alkaptonuria where homogenstisate is deposited in the connective tissue within cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Cardiovascular Health Study, which looked at 5621 patients aged 65 or older, 1.8% were found to have aortic stenosis [7]. A series of 76 patients with alkaptonuria found aortic stenosis in 25% of patients over 65 [3]. Interestingly, unlike degenerative calcific aortic stenosis, the presence of stenosis was not correlated with the standard cardiovascular risk factors or age related calcification but was moderately correlated with the extent of joint involvement, another manifestation of alkaptonuria where homogenstisate is deposited in the connective tissue within cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The disease usually manifests late in life after the 4 th decade due to decline in renal clearance with age. Rarely, alkaptonuria can have cardiovascular manifestations: with ochronosis described in the heart valves, aorta, pericardium, endocardium and coronary arteries [3][4][5]. Aortic stenosis is the most commonly reported cardiovascular manifestation with a number of case series describing an increase in the prevalence of aortic stenosis compared to the general population.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of aortic valve disease was reported significantly higher in patients with alkaptonuria. The two largest case studies to date include a series of 58 alkaptonuria patients, three (5.2%) of whom underwent aortic valve replacement, and a recent study by Hannoush et al of 76 alkaptonuria patients showing a 9% prevalence of aortic stenosis …”
Section: Discussionmentioning
confidence: 99%
“…Gaines and Pai suggested that the aortic valve dysfunction is caused by the degeneration of pigment‐laden fibrocytes, which may in turn stimulate progressive dystrophic calcification and fibrosis of leaflet tissue. Interestingly, there is no identifiable causal relationship between the conventional cardiovascular risk factors and the development of aortic valve disease …”
Section: Discussionmentioning
confidence: 99%
“…AKU is a multifaceted disease, with symptoms affecting individuals differently. Other features of AKU include arthritis, joint destruction, aortic stenosis, vascular calcifications, and dark urine due to the presence of HGA in the urine …”
Section: Introductionmentioning
confidence: 99%